DEVELOPING COMMUNICATIVE-BASED INSTRUCTIONAL MODEL OF SPEAKING SKILL IN ELEMENTARY SCHOOL - Muammar Muammar; Suhardi Suhardi; Ali Mustadi (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
This study aims to develop a communicative-based instructional speaking skill model, in respect to experts' validation, practicality, and effectiveness in learning. The learning process was generated due to the unavailability of an instructional speaking skill model, which was predicted to help students verbalize their thoughts, ideas, and feelings. The method used was research and development (R&D) technique, while the subjects included five experts/teachers and 26 students selected in the elementary school. Data collection were carried out through scale, observation, tests, and distribution of questionnaires, as well as analyzed descriptively and statistically, using a t-test method. The results showed that, the communicative-based instructional speaking skill model was practical, effective in improving students'verbal ability, and considered valid by the experts.